Chemical Constituents of the Marine Traditional Chinese Medicine of Pegasus laternarius Cuvier (Hai-E Yu) - Sun, Shuqian; Gao, Zhen; Wang, Mengxue; Chen, Sha; Guo, Wenjuan; Li, Xuwen (Pharmaceutical Fronts, 2024)
Pegasus laternarius Cuvier (Hai-E Yu) is a marine traditional Chinese medicine that has been used to treat cancers and reduce inflammation. Previous chemical investigations have only revealed the occurrence of high levels of protein, fatty acids, and a large number of steroids, thus more active compounds in P. laternarius still need to be further discovered. The present study aims to search for new bioactive constituents of P. laternarius with cytotoxic effects and nitric oxide (NO) inhibitory activities. In this work, 16 pure compounds from the ethyl acetate fraction of Pegasus laternarius Cuvier were successively obtained by various chromatographic techniques, and the structure of the isolates was elucidated by spectroscopic analyses. The isolated and identified compounds included one 2H-1,2,3-triazole-4-carboxylate derivative (1), two oxadiazines (2, 3), two amino acids (4, 5), three nucleosides (6–8), three steroids (9–11), and five others (12–16). All the obtained compounds were evaluated for their antitumor activity on A549 and HCT-116 cell lines along with their inhibitory effects on lipopolysaccharide-induced NO production in RAW264.7 cells. The triazole compound 1 was found to exhibit moderate cytotoxicity against two human cell lines (A549 and HCT-116) with IC50 values of 44.5 and 32.9 μmol/L, respectively. The steroid compound 10 inhibited NO production with IC50 values lower than 50 μmol/L. Consequently, this study provides insight into the cytotoxic and NO inhibitory activities of the marine traditional Chinese medicines in Hai-E-Yu.
Keywords: marine traditional Chinese medicine; Pegasus laternarius Cuvier; cytotoxicity; anti-inflammatory